BIOLOGI REPRODUKSI IKAN SEPATUNG, Pristolepis grootii Blkr. 1852 (NANDIDAE) DI SUNGAI MUSI [Reproductive biology of Indonesian leaffish, Pristolepis grootii, Blkr. 1852 (Nandidae) in Musi River] - Y. Emawati; Siti Nurul Aida; H. A. Juwaini (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2009)
Pristolepis grootii is one of the fishes in Musi River. The objective of this study was to determine the information on reproduction biology of P. grootii, including sex ratio, condition factor, GI, GSI, fecundity, egg diameter, and the spawning pattern. The study was conducted in June, July, August, and September 2006 in 62 stations. P. grootii was found in 16 stations. The fishes were caught using the hand net and gill net. Total samples were 110 individuals comprised 69 (62.7%) males and 41 (37.3) females. The range of total length is between 50-145 mm. The pattern of the growth is positive allometric. The range of the condition factor for male fish is bigger in than the female one in every research month. The sex ratio for male and female fish is 1 : 1,68. The GI of female fish (0,037-4,217%) is heavier than the male one (0-2,247%). Fecundity is about 2.301 eggs. The diameter of the egg is 0.36-0.91 mm and the fish is indicated to be a total spawner.